Market Reaction to MSCI's Free Float Calculation Change: Evidence from LQ45 Companies - Raden Hendri Gusaptono; Ayesha Salsabila (Politeknik Siber Cerdika Internasional, 2026)
Background: The 2025 MSCI free float methodology change created observable pressure in the Indonesian stock market. This study examines reactions to this unique index methodology event using abnormal return, trading volume activity, and investor transaction patterns. Objective: This study aims to examine the Indonesian stock market’s reaction to the announcement of changes in MSCI’s free float calculation methodology using stock data from companies included in the LQ45 index. Methods: This study employed an event study design with a 21-day observation window. The research sample was selected using purposive sampling, resulting in 38 eligible companies. Hypothesis testing was conducted using the one-sample and paired-sample Wilcoxon signed-rank tests. Results: The findings indicate a significant abnormal return around the event date (t0), but no significant difference in abnormal returns before and after the event. A significant difference was observed in trading volume activity. Descriptive analysis revealed a shift in transaction patterns, with foreign investors exhibiting net selling activity and domestic investors demonstrating net buying activity around the event period, although the difference was not statistically significant. Conclusion: These findings indicate that the free float methodology announcement was primarily reflected in market transaction dynamics rather than persistent abnormal returns. This study provides new empirical evidence for the event study literature and contributes to the understanding of semi-strong form market efficiency in emerging capital markets.